Aqueous phase reforming of sorbitol over sonosynthesized ca-doped ni supported on al2o3 and tio2 for production of value added chemicals - Mohamad Razlan, Md Radzi; Muhammad Azizi, Topek; Mohammad Tazli, Azizan; A., Ramli; S. Zainal, Abidin (Universiti Malaysia Pahang, 2018)
Production of value added chemicals derived from renewable carbohydrate such as sorbitol through the aqueous phase reforming is a promising technology. Aqueous phase reforming for industrial without highly effective and efficient catalyst in term of its operational lifetime and catalytic activity. Supported nickel catalyst has been identified have good selectivity of alcohols for aqueous phase reforming of sorbitol, and support such as Al2O3 and TiO2 has been identified as support which has good surface area and active sites. In this work, the effect of introducing the varying percentage of Ca (0%, 0.5%, 3% and 5%) as promoter onto 10% Ni supported on two potential catalyst support, TiO2 and Al2O3 have been investigated. The catalysts are prepared via the sonochemical method, where the catalysts are synthesized under ultrasonic irradiation for 45 minutes using ultrasonic probe at 90W using methods by Abdollahifar, et al. [1], where sonochemical method has discovered to enhance the dispersion of particles, improve surface area and increase the performance. The sonosynthesized catalysts were then subjected for characterization by using Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM), Xray Powder Diffractometer (XRD)